Factors Related To The Occurrence Of Ari In Toddlers At Telaga Dewa Health Center In Bengkulu City In 2024 - Oksidistri, Oksidistri; Suyanto, Jipri; Surahman, Fery; Habibi, Julius; Retni, Retni (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Intoduction: Acute Respiratory Infections (ARI) are acute infectious diseases that affect one or more parts of the respiratory tract. It can be caused by bacteria or viruses that enter the respiratory tract and cause an inflammatory reaction. According to the World Health Organization (WHO), the mortality rate among toddlers due to ARI is 15%-20% in developing countries. The incidence rate of ARI in Indonesia is relatively high at 53%, with 31.4% occurring in toddlers. In Bengkulu City, there were 3,240 cases in 2022, with the highest number of cases (2,404) reported at the Telaga Dewa Health Center. The aim of this study is to identify the factors related to the incidence of ARI in toddlers at Telaga Dewa Health Center, Bengkulu City, in 2024. Method: This study uses a cross-sectional research design. The population in the study consisted of 183 toddlers, and the sample was taken using purposive sampling with a total of 65 toddlers. The research location is at Telaga Dewa Health Center. Result and Discussion: he tests used include univariate and bivariate tests, with data analysis conducted using the chi-square test. The analysis results show that the majority of respondents (55.4%) had inadequate home ventilation, (52.3%) had adequate flooring, (50.8%) had adequate walls, (56.9%) had abnormal nutritional status, and (53.8%) had incomplete immunization. There is a relationship between home ventilation and the incidence of ARI in toddlers with a p-value of (0.013), nutritional status with a p-value of (0.007), and immunization with a p-value of (0.022). Meanwhile, there is no relationship between flooring and the incidence of ARI in toddlers with a p-value of (0.335), and between walls and the incidence of ARI in toddlers with a p-value of (0.879). Conclusion: It is hoped that Telaga Dewa Health Center can prepare guidelines for counseling on risk factors related to the incidence of ARI and optimize preventive and promotional programs regarding factors related to the incidence of ARI.